ANALISIS KINERJA PEDAGANG PASAR ALAI DAN FAKTOR YANG MEMPENGARUHINYA - Mery Trianita; Yuhelmi Yuhelmi (Jurnal Apresiasi Ekonomi, 2017)
This study was conducted to determine how the influence of the initial capital, long effort and hours of work on the performance of the market traders alai Padang. The respondents are all traders who sell in the market of alai which has shops , a variety of types of businesses and turnover are almost the same. Sampling done by the census where all the population into the sample in this study as many as 56 people traders. To test the hypothesis, this research uses multiple linear regression analysis. The results of the analysis obtained that the initial capital and long efforts has a significant influence on the Performance of the market traders alai. While working Hours have no effect on the performance of the market traders Alai. Keywords : Initial Capital, Long Effort and Hours of Work